Cinema documentário e escrita da história: os filmes do conflito em Oka de Alanis Obomsawin - Kosteczka, Luiz Alexandre Pinheiro [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This dissertation aims to analyze four audiovisual documents of Alanis Obomsawin. Kanehsatake: 270 Years of Resistance, My Name is Kahentiiosta, Spudwrench: Kahnawake Man e Rocks at Whiskey Trench, are four documentaries from a director living in Canada since her childhood. Produced during the 90‟s, these films sought to narrate de event known as “Oka‟s conflict”, in which the native population from Kanehsatake and Kahnawake clashed the Canadian State. From the contemporary historiography concerns this work seeks to indicate the relations between the cinematography and historiographical discourses. Thereby, three frameworks compose the reflections of this text: the temporal questions of the discourse about an event; the problematic of memory and testimony; and the questioning to the concept of representation in the documentary film. Thus, this dissertation quest for appraise the discursive dimensions of these four documentaries, comprehending the corollaries of these audiovisual exemplars to the writing of history

Esta dissertação pretende analisar quatro documentos audiovisuais de Alanis Obomsawin. Kanehsatake: 270 Years of Resistance, My Name is Kahentiiosta, Spudwrench: Kahnawake Man e Rocks at Whiskey Trench, são quatro documentários de uma realizadora radicada no Canadá desde sua infância. Produzidos durante a década de 1990, esses filmes procuraram narrar o evento conhecido como “O conflito de Oka”, no qual, populações nativas de Kanehsatake e Kahnawake se embateram com o Estado canadense. A partir de questionamentos pertinentes à historiografia contemporânea, esse trabalho de pesquisa intende indicar as relações entre o discurso cinematográfico e o historiográfico. Dessa forma, três eixos constituem as reflexões desse texto: as questões temporais do discurso acerca de um evento; a problemática da memória e do testemunho; e o questionamento ao conceito de representação no filme documentário. Assim, essa dissertação procura arguir a respeito das dimensões discursivas desses quatro documentários, compreendendo as implicações desses exemplares audiovisuais para com a escrita da história
Keywords: Documentario (Cinema); Historiografia; Cinema e história